Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1365-2648.1994.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Social networks: their relevance to mental health nursing

Abstract: Research into social networks has been advancing over several decades, originally in relation to the general population and more recently in relation to their influences on health and mental health. The recent full implementation of the Community Care Act, with its stress on the role of carers and networks, reinforces the need for mental health nurses to be aware of these issues. This selective review examines some of the ways in which social networks can be analysed, explores the relationship between social n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…In other words, people with high levels of selfefficacy not only perform better in exercise but demonstrate better exercise behavior (Chung, 1999). Simmons (1994) defines social support as a form of interpersonal interaction which provides psychological support or specific aid to help solve a problem, where the helper mainly comes from among personal social connections, not from complete strangers; in the meantime, social supporters also take part in the process of sharing, giving and taking. Nies, Vollman, and Cook (1998) studied the exercise behaviors of European women using a qualitative method and found that social support is one of the major promoting factors of exercise behavior and an important explanatory variable in women's exercise behavior.…”
Section: Self-efficacy In Exercisementioning
confidence: 99%
“…In other words, people with high levels of selfefficacy not only perform better in exercise but demonstrate better exercise behavior (Chung, 1999). Simmons (1994) defines social support as a form of interpersonal interaction which provides psychological support or specific aid to help solve a problem, where the helper mainly comes from among personal social connections, not from complete strangers; in the meantime, social supporters also take part in the process of sharing, giving and taking. Nies, Vollman, and Cook (1998) studied the exercise behaviors of European women using a qualitative method and found that social support is one of the major promoting factors of exercise behavior and an important explanatory variable in women's exercise behavior.…”
Section: Self-efficacy In Exercisementioning
confidence: 99%
“…This may be considered in terms of the nature of the relationships, e.g. friends, neighbours, parents etc., the closeness of these relationships and the degree of reciprocity which exists between network members (for a comprehensive review of social networks see Simmons 1994).…”
Section: Characteristics Of Social Network For People Suffering Frommentioning
confidence: 99%
“…Although Ms. A had only six key ties in her network, potentially she could have many others from school, work, her neighborhood, and her extended family. The density of a network is determined by the levels of interconnectedness among network members (Bott, 1971) and the extent to which members of the network maintain contact with one another (Bott, 1971;Simmons, 1994). Like Ms. A, other seriously mentally ill clients tend to have fewer clusters of closely connected people (Hammer, 1981).…”
Section: Network Size and Densitymentioning
confidence: 98%